Graphene Oxide: Liquid Crystals of Graphene Oxide: A Route Towards Solution‐Based Processing and Applications (Part. Part. Syst. Charact. 9/2017). (22nd September 2017) - Zhang, Jizhen; Seyedin, Shayan; Gu, Zhoujie; Salim, Nisa; Wang, Xungai; Razal, Joselito M.
Abstract : In article number1600396, Shayan Seyedin, Joselito M. Razal, and co‐workers discuss recent exciting advances in the synthesis, solution processing, and applications of graphene oxide liquid crystals. Some perspectives on the challenges and opportunities of graphene oxide liquid crystals for novel architectures are discussed to provide insights for the future directions of the field.